2004
DOI: 10.1111/j.1460-9592.2004.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal agenesis: management of the first 10 months of life

Abstract: Tracheal agenesis is a potentially lethal congenital anomaly, appearing only at birth. We describe a newborn preterm infant who presented with immediate respiratory distress and no audible cry. There was almost complete tracheal agenesis with a very short segment of distal trachea (only two tracheal rings) arising from the anterior wall of the esophagus, before dividing into the mainstem bronchi. The anomaly was unsuspected prenatally, as the scan showed pyloric atresia and complex congenital cardiac disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In 1979, Faro et al reported a more detail classification of tracheal agenesis (7 types) based on the literature review [3]. To our best knowledge, 144 cases of tracheal agenesis, including 19 of type I, 87 of type II and 38 of type III, have been reported in the English literature [4][5][6][7][8][9][10][11]. In 1963 Fonkalsrud et al reported a case who survived for 6 weeks after reconstructive surgery including trachealizing the esophagus,dividing the distal esophagus and inserting a gastrostomy tube [12].…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, Faro et al reported a more detail classification of tracheal agenesis (7 types) based on the literature review [3]. To our best knowledge, 144 cases of tracheal agenesis, including 19 of type I, 87 of type II and 38 of type III, have been reported in the English literature [4][5][6][7][8][9][10][11]. In 1963 Fonkalsrud et al reported a case who survived for 6 weeks after reconstructive surgery including trachealizing the esophagus,dividing the distal esophagus and inserting a gastrostomy tube [12].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases depending on the existence of a fistula ventilation via an oesophageally placed tube is possible (see also case 3). Mostly these infants die during the first days of life although there are descriptions in the literature of children who survived the neonatal period [1,5,10,11] with a diverse quality of life. Soh et al [11] reported a girl with a Floyd type 1 and a tetralogy of Fallot, who died at the age of 6 years and 10 months due to unstoppable oesophageal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…At the age of 2 and again at 3 years he had major operations to the oesophagus. The other three children reported in the literature had a follow-up until 10 [1] and 15 months of age [10]. They all underwent major surgical interventions and have tracheostomies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reported newborns with tracheal agenesis expire postnatally and long-term survival is rare [1]. However, if tracheal agenesis is considered during resuscitation, intubation of the oesophagus and ventilation via a bronchooesophageal fistula is an option to manage these patients until an exact diagnosis can be made.…”
mentioning
confidence: 99%